Modeling of Ethylene Glycol Production from Glucose in a Semi‐Continuous Reactor. Issue 5 (2nd April 2020) - Murillo, Carlos; Irakoze, Ghislain; de Oliveira Vigier, Karine; Delmas, Michel; Jérôme, François; Pérès, Yolande; Urrutigoity, Martine; Cognet, Patrick
Abstract: A numerical study describes the catalytic conversion of glucose into ethylene glycol (EG) in a semi‐batch reactor. This analysis couples a set of power law models (homogeneous reactions) and Langmuir‐Hinshelwood‐Hougen‐Watson (LHHW) equations (hydrogenations). For this purpose, the kinetic parameters of the LHHW expressions are estimated for the reaction conditions. Then, the kinetic model evaluates the influence of the H2 pressure and the catalyst concentrations on the selectivity. The results indicate that the EG yield is increased by setting the temperature and the H2 pressure. In this manner, the process reduces the hexitols and methane production and increases the EG yield. The originality of the work is based on the influence of the H2 pressure and the catalyst concentrations in the model. Abstract : A combined kinetic model for the conversion of glucose into ethylene glycol (EG) allows analyzing the influence of operating conditions on the reaction yields. The kinetic parameters of the hydrogenation rate laws were adjusted to the temperature range which enhances EG production. The developed numerical model was applied to evaluate glucose conversion and selectivity in a semi‐batch reactor.